Cultural Literacy and Physics Concepts Based Ethnophysics on Gender in the Jong Boat Game Culture of Rupat - Z, Fakhruddin; Syidik, Muhamad; Nasir, Muhammad (Kasuari: Physics Education Journal (KPEJ), 2025)
This study aims to determine the level of cultural literacy and physics concept literacy of students towards the traditional game of Perahu Jong with an ethnophysical approach, and to analyze differences in abilities based on gender. The study was conducted on Rupat Island using a survey method and proportional stratified random sampling technique. The sample consisted of 109 ninth grade students from SMPN 2 and SMPN 3 Rupat. The instruments used were cultural literacy and physics concept literacy tests. The results of the descriptive analysis showed that the average cultural literacy ability of students was low with a score of 50.4, while physics concept literacy was very low with an average score of 32.9. The results of the Mann-Whitney U test showed a significant difference between the cultural literacy of male and female students, where female students had a higher score. However, there was no significant difference in physics concept literacy between male and female students. These findings indicate the importance of implementing local culture-based physics learning as a contextual approach to improving students' scientific literacy and preserving regional culture.